THE ROLE OF COOPERATION AND SMEs DEPARTMENT IN EFFORTS TO DEVELOP MSME PRODUCTS THROUGH THE “UMKM JUARA” PROGRAM IN SUKABUMI CITY - Nenden Tari Fithriati; Rizki Hegia Sampurna; M. Rijal Amirulloh (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
Micro, Small and Medium Enterprises are an important sector and have a large contribution in realizing regional economic development. In this case, it contributes 60 percent to GDP and is able to absorb labor up to 97.22 percent. Therefore, the West Java Provincial government created a program